2014
DOI: 10.1007/s11882-014-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Audiovestibular System in Children with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus can affect inner ear by disrupting either the hearing or balance system. Affection of hearing can be anatomically categorized into conductive and sensorineural hearing loss, while affection of the equilibrium system manifests either as an isolated manifestation like vertigo or as a part of a spectrum like Meniere's disease. Most cases show asymptomatic affection requiring an objective audiovestibular assessment. More focus should be given to routine evaluation especially with disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…A few authors 22 , 23 have described vertigo in patients with SLE and, in all cases, this symptom was always associated with SNHL or tinnitus. Gad and Abdelateef 24 found that vertigo in children with SLE was always associated with cochlear symptoms. However, the incidence of vestibular symptoms may be under-reported due to the slowly progressive onset of these symptoms and compensation by the somatosensory system and vision.…”
Section: Audiovestibular Disorders In Patients With Slementioning
confidence: 99%
“…A few authors 22 , 23 have described vertigo in patients with SLE and, in all cases, this symptom was always associated with SNHL or tinnitus. Gad and Abdelateef 24 found that vertigo in children with SLE was always associated with cochlear symptoms. However, the incidence of vestibular symptoms may be under-reported due to the slowly progressive onset of these symptoms and compensation by the somatosensory system and vision.…”
Section: Audiovestibular Disorders In Patients With Slementioning
confidence: 99%
“…Balance disorders as a consequence of SLE have been observed also in children [37]; however, the incidence of vestibular symptoms may be underestimated due to their slowly progressive onset and consequent compensation by the somatosensory system and vision.…”
Section: Inner Ear Involvement In Autoimmune Diseasesmentioning
confidence: 99%
“…Vestibular complications are quite common in patients with SLE (19). One study showed that the incidence of abnormal findings on electronystagmography in patients with SLE was significantly higher than in healthy control patients (20).…”
Section: Discussionmentioning
confidence: 99%